'Greek Foreign Policy and the Middle East; from possibility to fulfillment?' - EKAVI ATHANASSOPOULOU (Byzantine and Modern Greek Studies, 2010)
The topic of this article is the historical evolution of Greek foreign policy in the Middle East over the past thirty-five years. It essentially seeks to explain the broad framework of conditions and objectives within which Greek foreign policy has been made towards the Arab Middle East and Israel. It argues that the amount of involvement of Greek foreign policy in the area was relatively little. Though much has changed in Greece's approach towards the Middle East since the 1990s, there is also a significant continuity of attitude, in the sense that serious attention has not been paid to this part of the world.